Influence of filler content on physicomechanical and bonding properties of an experimental dental resin cement. Issue 4 (14th May 2012) - Xiong, Jie; Sun, Xiang; Chen, Jihua; Tang, Lihui
Abstract: To investigate the effects of filler contents on the bonding and physicomechanical properties of experimental dental resin cements and the correlation between them, four groups were formulated with silicon dioxide filler in the following weight percentages: A: 40%, B: 50%, C: 60%, and D: 70%. LuxaCore dental resin cement was used as group E for commercial reference. For testing bond strength, resin cements were applied to the prefabricated dental fiber posts in the artificial teeth canal and photo cured, and then the microtensile bonding strength (BS) between posts and resin cement was measured in sticks of 1 × 1 mm 2 . For the mechanical properties, flexural strength (FS), diametral tensile strength (DTS), compressive strength (CS), and hardness (H) were tested according to the related standard. Water sorption and solubility were also determined. The results showed both bonding and physicomechanical strengths of the experimental resin cements varied to different extents with filler addition. Positive correlations existed respectively between the filler content and some mechanical properties ( r FS = 0.964, r CS = 0.967, and r H = 0.959), whereas no significant correlations were found between the filler content and the other strength values tested in this study ( r DTS = 0.321, r BS = 0.014), neither were between bond strength and mechanical properties. The effect of filler content on mechanical properties was more influential and prominent compared to that on bond strength. It is partial to compare properties and to predict clinical behaviors of resin materials based on a single in vitro test, and comprehensive evaluation is necessary. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :